Huffmanela cf. huffmani (Nematoda: Trichosomoididae) infecting swim bladder, peritoneum, and gonad of variable platyfish, Xiphophorus variatus (Cyprinodontiformes: Poeciliidae) and eastern mosquitofish, Gambusia holbrooki (Poeciliidae) in Florida; taxonomy, phylogenetic analysis, and pathological changes - Bullard, Stephen A; Moravec, František; Ksepka, Steven P; Warren, Micah B; Dutton, Haley R; Huffman, David G; Yanong, Roy P E (Parasitology research, 2022)
Variable platyfish, Xiphophorus variatus (Meek, 1904) (Cyprinodontiformes: Poeciliidae) and eastern mosquitofish, Gambusia holbrooki Girard, 1859 (Poeciliidae) from earthen ponds in west central Florida were examined for parasitic infections. At necropsy, we observed myriad nematodes (adults and eggs), which we identified as Huffmanela cf. huffmani, infecting the swim bladder, gonad, and visceral peritoneum. Nucleotide sequences (small subunit ribosomal DNA, 18S) of H. cf. huffmani from variable platyfish and eastern mosquitofish were identical; likewise for newly obtained 18S sequences of Huffmanela huffmani Moravec, 1987 from the swim bladder of red breast sunfish, Lepomis auritus (Linnaeus, 1758) (Centrarchiformes: Centrarchidae) and warmouth, Lepomis gulosus (Cuvier, 1829) from the San Marcos River (type locality for Huffmanela huffmani Moravec, 1987), Texas. The sequences of H. huffmani and H. cf. huffmani differed by 7 (1%) nucleotides. Pathological changes comprised proliferation of the tunica externa of the swim bladder in low-intensity infections in addition to inflammation, proliferation, and tissue necrosis of swim bladder, peritoneum, and gonad in high-intensity infections. The lesion was severe, affecting the cellular constituents of the swim bladder wall and reducing the size of the swim bladder lumen; potentially reducing swim bladder physiological efficiency. The present study is the first record of a freshwater species of Huffmanela Moravec, 1987 from beyond the San Marcos River, first record of a species of Huffmanela from a livebearer, first nucleotide sequences and phylogenetic analysis for Huffmanela, and first evidence that an infection by a species of Huffmanela causes pathological changes that could impact organ function.
Keywords: hlístice; Perciformes; močový měchýř; Fish Diseases; peritoneum; Nematoda; Urinary Bladder; fylogeneze; Pathology; Gonads; Phylogeny; Freshwater; Florida; Animals; zvířata; nemoci ryb; Aquaculture; Peritoneum; Cyprinodontiformes; gonády